Pipelines 2017. proceedings of sessions of the Pipelines 2017 Conference, August 6-9, 2017, Phoenix, Arizona - Pridmore, Anna B.; Geisbush, Jim (American Society of Civil Engineers, 2017)
"This collection contains 55 peer-review papers on the planning and design of pipelines for reliability and resiliency through sustainable design and construction. Topics include: risk and resilience; inspection mapping and surveying; rehabiliation; seismic events; trenchless techniques; asset management and case studies."-- ASCE website
Keywords: Pipelines -- Design and construction -- Congresses.; Trenchless construction -- Congresses.; Sustainable construction -- Congresses.; Pipelines -- Maintenance and repair -- Congresses.; elektronické knihy; electronic books